QUALITY ANALYSIS OF ENGLISH FINAL TEST FOR LIGHT VEHICLE ENGINEERING STUDENTS AT SMK NEGERI 1 NGULING - Firdaus, Maya Fitriyah; Setyowati, Lestari; Mabaroh, Barotun (J-ELLiT (Journal of English Language, Literature, and Teaching), 2021)
The purpose of this study is to investigate the quality of an English final test of SMKN 1 Nguling seen from its content validity, reliability, item difficulty, discriminating power, and effectiveness of distractor. The design of this study was qualitative research which focuses on content analysis and descriptive quantitative. The result shows that the test was considered sufficient. In particular, the researchers found out that the content validity of the test is very high, and the reliability of the test is moderate (r. 0.427). However, the test had poor item difficulty as half of the test items test was in the difficult category.  The test also has poor discriminating power.  Finally, in terms of the effectiveness of distractors, the result shows that 24 items need some revisions. The researchers concluded that even though the test is high in content validity and moderate in its reliability, the test still needs some improvements, especially in discriminating power and item distracter.